Deriving a policy document towards an early warning system for estuaries in South Africa: case study Great Brak estuary, Eden District, Southern Cape - Stander, Johan (Department of Oceanography, 2020)
South Africa's estuaries and their surrounding communities are becoming increasingly vulnerable to storm surges and accompanied estuary flooding. These events are largely due to increasing severity of storm surges combined with growing housing and commercial developments. A particularly severe weather event in 2007/2008 highlighted the pressing need to understand the processes involved and the urgency to develop proactive response and management actions to mitigate the effects of future storm events on these coastal areas. Scientific research on estuarine flooding is limited not only for South Africa but within the international community as well and only recently has received committed attention from policy makers. It is clear that our current knowledge of South African estuary flooding events remains rudimentary; while necessary action to mitigate such events are poorly understood and planned. The aim of this PhD thesis is to devise and implement an Estuary Early Warning – Emergency Preparedness and Response Guide for stakeholders and government policymakers. This guide will target South Africa's coastal region by analysing past information on storm surges and estuary flooding, particularly in the low-lying southern coast region of the Western Cape, South Africa. The key objective of this thesis is to assess the best processesfor the issuing of estuary alerts and to better standardise them so that the response remains in line with multi-hazard early warning standard procedures and practices within South Africa. A further aim is to provide a comprehensive national guideline on how best to effectively disseminate and communicate such information and to establish an Estuary Early Warning (EEW) – Emergency Preparedness and Response Guide (EPRG), which forms part of the South African Multi-Hazard Early Warning System (MHEWS). It is critical that this EEW meets general principles accepted internationally for an effective Early Warning System. This thesis addresses the following key elements namely: (1) Risk identification, (2) Key drivers and contributions to estuary flooding, (3) Monitoring and alert early warning system, (4) Alert dissemination and (5) Response actions. Such pioneering work is an essential tool to translate science into policy, a crossover field, which remains poorly implemented.